Вплив логістичних процесів на ефективність управління запасами підприємства - Іпполітова, Інна Ярославівна; Білоцерківський, Олександр Борисович; Гудименко, Вячеслав Павлович (My University, 2024)
У статті розглянуто теоретичні підходи щодо визначення сутності категорії «управління запасами підприємства» різними науковцями та зазначено відмінності, які вони вкладають в це визначення. Розглянуто, які системи управління запасами є найбільш розповсюдженими, зазначено їх сутність, переваги та недоліки використання. Обґрунтовано необхідність вибору оптимальної системи управління запасами для підприємства з метою підвищення ефективності його функціонування через призму логістичних процесів. Визначено особливості застосування різних систем управління запасами підприємства, що враховують логістичні процеси, їх переваги та потенційні можливості застосування. Запропоновано послідовність формування та вибору системи управління запасами підприємства з урахуванням логістичних процесів, від якого залежить можливість забезпечення узгодженого, ефективного та економічно доцільного функціонування підприємства.

The article examines theoretical approaches to defining the essence of the category of "enterprise inventory management" by different scientists, highlighting the variations in their definitions. Inventory management is crucial for any enterprise, especially in a highly competitive and rapidly changing market, and takes on decisive importance under the complex conditions of a full-scale invasion of Ukraine. The study employs general scientific research methods such as theoretical generalization, analysis, synthesis, and induction. It considers the most common inventory management systems, noting their essence, advantages, and disadvantages. The necessity of selecting the optimal inventory management system to enhance enterprise efficiency through logistics processes is substantiated. The choice of an inventory management system depends on several factors that must be considered to ensure optimal resource management, minimize costs, and improve enterprise efficiency. The article identifies the features, advantages, and potential applications of various inventory management systems that incorporate logistics processes. Enterprises that consider logistics processes in inventory management can more quickly adapt to market changes, new customer demands, or supply chain alterations, providing greater flexibility in responding to external and internal challenges. The use of information and communication technologies in inventory management allows enterprise management to obtain more accurate and timely data for decision-making. The proposed sequence for forming and selecting an enterprise inventory management system, considering logistics processes, aims to ensure coordinated, effective, economically feasible operation of the enterprise while maintaining a high level of customer service, reduce costs, minimize risks, and enhance the enterprise competitiveness in the long term. The practical significance of the article lies in the potential implementation of the proposed sequence for selecting an inventory management system in the practical activities of enterprises, tailored to their specific needs.
Logistics processes influence on the efficiency of the enterprise inventory management
Keywords: запаси; управління запасами підприємства; логістичні процеси; системи управління запасами; логістика; логістичне управління запасами; inventory; enterprise inventory management; logistics processes; inventory management systems; logistics; logistics inventory management